Challenges in the Management of Ectopic Parathyroid Pathologies: A Case Series of Five Patients - Adem Binnetoğlu; Berat Demir; Javahir Mamadlı (Turkish Archives of Otorhinolaryngology, 2020)

(untitled)
In primary hyperparathyroidism (PHPT) the diagnosis and treatment of ectopic parathyroid adenomas (EPTA) is a challenging process for head and neck surgeons. We present five patients with EPTA in different locations, along with an in-depth discussion of imaging modalities. We used sestamibi scintigraphy (MIBI) and ultrasound as first line imaging tools in asymptomatic hypercalcemia and PHPT. Single photon emission computed tomography (SPECT) was combined with MIBI or computed tomography (CT) if a parathyroid pathology was not localized initially. Four-dimensional parathyroid CT (4D-CT) was the last imaging modality preferred to localize the ectopic parathyroid gland. We performed focused unilateral neck exploration (FUNE) with intraoperative frozen section analysis as a routine procedure for imaging-detected lesions. Bilateral neck exploration was performed for re-exploration cases and imaging-negative cases. Histopathology confirmed EPTA and postoperative serum calcium normalized in all cases. 4D-CT is promising for ectopic parathyroid gland localization if all other imaging modalities fail. Despite the advancements in imaging, surgical experience continues to play the central role in the management of ectopic parathyroid pathologies.